Bronchiolitis obliterans - King, Talmadge E. (Lung, 1989)
Bronchiolitis obliterans in the adult patient is a relatively uncommon and vexing clinical entity. This confusion results because this pathologic finding occurs in a variety of diverse clinical settings. Bronchiolitis obliterans is a fibrotic process that primarily affects the small conducting airways. The lesion results from damage to the bronchiolar epithelium and the repair process leads to excessive proliferation of granulation tissue. The alveoli adjacent to the small airway are almost always involved; however, a considerable portion of the interstitium is usually spared. The findings in these patients may physiologically and radiographically mimic chronic obstructive pulmonary disease (COPD). On the other hand, some of the processes associated with bronchiolitis obliterans result in restrictive or mixed restrictive and obstructive ventilatory defects; consequently, they may be confused with other diffuse infiltrative lung disorders. This review will focus principally on bronchiolitis obliterans in adults, which, until recently, was considered rare. There has been heightened interest in this process in adults because of its association with the connective tissue diseases, its development following toxic fume exposure, its occurrence as a result of chronic graft versus host reactions, and the increasing recognition of patients with idiopathic forms of the disease that have an insidious onset often confused with more common problems such as COPD or idiopathic pulmonary fibrosis.